The relationship between stocking eggs in boreal spawning rivers and the abundance of brown trout parr - Syrjänen, Jukka Tapani; Ruokonen, Timo Juhani; Ketola, Tarmo; Valkeajärvi, Pentti (Oxford University Press, 2015)
Stocking with eggs has been widely used as a management measure to support degraded salmonid stocks. In Finland, Atlantic salmon and both seamigrating and lake-migrating brown trout are stocked as eggs, alevins, fry, parr, and smolt, whereas trout are also stocked as mature fish. The aim of this stocking is to improve catches and to support collapsed spawning stocks. We assessed the success of stocking with brown trout eggs in a study of 17 Finnish boreal forest rivers, of which 9 were subject to egg stocking. All rivers contained some naturally spawning trout. In 16 rivers, including non-stocking years and unstocked rivers, egg stocking did not increase the total (wild and stocked) density of 0-year-old parr. However, those rivers with higher existing trout densities in non-stocking years seemed to benefit most from stocking, suggesting some role of river-specific extrinsic factors affecting egg-to-parr survival. In one river monitored for 14 years, only a weak correlation was found between the total density of 0-year-old parr and the number of eggs stocked. However, in nine parr samples from five rivers, the mean proportion of parr derived from stocked eggs was 40%. The mean survival to first autumn parr of egg-stocked and wild individuals was 1.0 and 3.3%, respectively. Probable reasons for the detected low to moderate impact of egg-stocking are (i) large variation in total parr density between years and rivers, (ii) small number of stocked eggs, (iii) placing egg boxes and egg pockets in unsuitable microhabitats, and (iv) unsuitable emergence time of egg-stocked individuals, or other extrinsic factors creating extra mortality. We recommend field and laboratory experiments to improve and standardize stocking methods, and monitoring the connection of wild spawning stocks and parr recruitment. Finally, we encourage fishery authorities to create clear management goals for threatened wild salmonid stocks.
Keywords: alevin; Alizarin red; egg pocket; egg box; otolith; redd; Salmo trutta; stock management; survival